The Islamic Movement in Malaysia: Historical Context and Factors - Ahmad Nabil Amir; Tasnim Abdul Rahman (UMSU, 2023)
This study highlights the early history of the development of Islamic movements in Malaysia since colonial times. It looks at this from two important and overlapping angles: the islah movement that brought about national consciousness and aspirations for renewal and tajdid, and the influence of the anti-colonial movement and pioneering Islamic politics in the overseas archipelago. This study was qualitative in nature in terms of literature review and content analysis. The data was collected based on the documentation method by applying interpretive, analytical, descriptive, historical and comparative methods of analysis. The study formulates that the preached struggle has brought about significant changes in strengthening the movement and foundation (khittah), illuminating the spirit and soul of freedom, promoting the discourse of Islah and Islamising science. It has revealed the contribution and understanding of Islam that is complete and convincing in working on explicit political and socio-cultural bases and directions, and revealed the height of influence and idealism that extends in the tradition of intellect and civilisation, as well as efforts to build cadres at all levels.